Haitian Problem : illegal migration to the Bahamas - Marshall, Dawn I (UWI. Institute of Social and Economic Research KingstonJM, 1979)
Describes Haitian environment that provides the stimuli for the peasant to migrate. Gives brief history of illegal migration to the Bahamas examining characteristics and conditions of migrants. Describes actual conditions in the Bahamas - the migrant's destination. Discusses isolation of Haitian migrants living in camps separated from local settlements. Presents case study of Haitians living in the Carmichael area of New Providence, Bahamas.